Bifurcation of the Owner and Operator Analysis Under CERCLA: Finding Order in the Chaos of Pervasive Control - Lynda J. Oswald (Washington University Law Quarterly, 1994)
This Article focuses primarily on the liability of parent corporations under CERCLA, in part because the cases involving parent corporations raise typical types of issues in relatively uncomplicated factual circumstances. In addition, the cases involving parent corporations are plentiful enough to provide a good sample for evaluation, but limited enough to be manageable.
Keywords: Businessmen; Corporate directors; Disregarding corporate entity; Toxic torts; Comprehensive Environmental Response; Compensation; and Liability Act of 1980; United States; Liability for hazardous substances pollution damages